“Hit vs. violent”: the interactive effect of language abstraction and describer’s power on audience’s perception of communication accuracy - Chen, Fan Xuan (2017)
Language is an essential tool for our daily communications. Based on the Linguistic Category Model and the established works on power-abstraction relationship, this study examined the interactive effect of language abstraction and describers’ power on the audience’s perception of communication accuracy. We showed participants a series of behavioral scenarios depicting targets performing ambiguous behaviors, and the ambiguous behaviors were later either described abstractly or concretely by high or low-power describers. Then, we measured participants’ perceived description accuracy and perceived describers’ attitudes towards the target. We found that in the high-power describer condition, the abstract descriptions were perceived to be more accurate than concrete descriptions. We did not observe any simple effects of language abstraction on the perceived description accuracy in the low-power describer condition. We also noticed an interaction effect between description valence and language abstraction on participants’ perceived describers’ attitudes toward the target. Replicating previous studies, the effect of description valence on participants’ perceived describers’ attitude towards the target was found to be larger in the abstract (vs. concrete) language condition. Altogether, our results showed that levels of language abstraction may interact with the describers’ power in affecting participants’ perceptions of the communication accuracy and validity, whereas the description valence and language abstraction may interact to implicate on participants’ perception of the describers’ attitude towards the target. We also discussed the implications and limitations of the study, as well as suggestions for future research.